Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1109/jsac.2017.2726218
|View full text |Cite
|
Sign up to set email alerts
|

Resource optimization and power allocation in in-band full duplex-enabled non-orthogonal multiple access networks

Abstract: Abstract-In this paper, the problem of uplink (UL) and downlink (DL) resource optimization, mode selection and power allocation is studied for wireless cellular networks under the assumption of in-band full duplex (IBFD) base stations, nonorthogonal multiple access (NOMA) operation, and queue stability constraints. The problem is formulated as a network utility maximization problem for which a Lyapunov framework is used to decompose it into two disjoint subproblems of auxiliary variable selection and rate maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…The use of Matching Theory [27] -a mathematical framework from labor economics that attempts to describe the formation of mutually beneficial relationships over time-, has recently garnered a considerable interest in the context of resource allocation for wireless networks [28] with applications as varied as V2V communications [29], [30], FD-NOMA/OMA [31] or Fog computing [32]. However, for the sake of completeness we will first provide several definitions to properly address the fundamentals of this framework adapted to the problem at hand.…”
Section: Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Matching Theory [27] -a mathematical framework from labor economics that attempts to describe the formation of mutually beneficial relationships over time-, has recently garnered a considerable interest in the context of resource allocation for wireless networks [28] with applications as varied as V2V communications [29], [30], FD-NOMA/OMA [31] or Fog computing [32]. However, for the sake of completeness we will first provide several definitions to properly address the fundamentals of this framework adapted to the problem at hand.…”
Section: Schedulingmentioning
confidence: 99%
“…Phase I -Interference learning and candidate chunk selection • Each u ∈ U, updatesÎ u (t) as per (31) and reports channel in the UL. • In the edge controller, queues in {χ(t)} u∈U are updated by solving (22), (24).…”
Section: Algorithm 1: Hd Chunk Scheduling Between Sbss and User-clustersmentioning
confidence: 99%
“…The problem in (8) actually belongs to the class of the General Linear Fractional Programming (GLFP) problem. Due to the characteristics of functions f n (x), ξ n (x) and ψ(x), this problem is a non-concave optimization problem.…”
Section: B Physical Layer Model For Noma Systemmentioning
confidence: 99%
“…Many studies have been carried out to analyze and improve performance of NOMA systems [2], [3], [5], [6], [7], [8]. The authors in [2] showed that NOMA can outperform OMA in terms of spectral efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initialization of the cluster bandwidths, which are independently executed by each BS in the order of OpU c log U c q, bandwidth and power allowances of clusters are updated by outer and inner while loops, respectively. The inner loop is processed by BSs in a parallel fashion, where optimal powers and Lagrange multipliers are first calculated by (11)- (13) and (15)-(17), respectively. Notice that calculations of (11) and (13) is the most time consuming part of the while loops and it can be given for BS c as O`2 ř r pK r c´1 q˘.…”
mentioning
confidence: 99%